The Mysticism of Prophethood and Messengership: Studies in the Light of Sufi Barkat Ali Ludhianwi: عرفانِ نبوت و رسالت: مطالعاتِ صوفی برکت علی لودھیانویؒ کی روشنی میں - Zafar, Muhammad Ahmed; Abbas, Prof. Dr. Humayoon (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
This research article explores the essential dimensions of faith in the Holy Prophet Muhammad ﷺ through the lens of the teachings of Hazrat Abu Anees Sufi Barkat Ali Ludhianwi. It emphasizes that before fulfilling the requirements of faith in the Prophet ﷺ, a believer must attain a deep understanding of his reality. Drawing from Maqalat-e-Hikmat, the article presents Sufi Barkat Ali’s unique mystical approach to the concepts of Ma'rifat al-Nubuwwah, advocating that sincere recognition of the Prophet ﷺ is the cornerstone upon which the fulfilment of all religious obligations rests. The study elaborates on six key aspects derived from Sufi Barkat Ali’s teachings: (1) the Kāmiliyyah and Akmalīyyah (perfection and completeness) of the Prophet’s ﷺ person, Sunnah, Hadith, religion, and Prophetic medicine; (2) his Awwaliyyah, Nūrāniyyah, and Lawlākiyyah—that he ﷺ is the first of creation and the reason for all existence; (3) his Ummiyyah and 'Ilmiyyah, emphasizing his divinely granted knowledge despite not receiving worldly instruction; (4) his universal mission ('Ālamiyyah and Āfāqiyyah) as a mercy to all of creation; (5) the exalted Shān (dignity) of the Prophet ﷺ, which surpasses human comprehension; and (6) the doctrine of Khatm-e-Nubuwwah (Finality of Prophet hood), which Sufi Barkat Ali presents as the culmination of divine mercy upon humanity.